The sturlung era in modern Icelandic historical prose: Einar Kárason - Olga Markelova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The period from 1220 to1262-64, the so-called Sturlung era, is significant in Icelandic culture, not only due to its dramatic political events, but also because by that time the great works of the Old Icelandic literature have been written down. In modern Icelandic historical fiction the most noticable text, devoted to the Sturlung era, is the tetralogy by Einar K?rason ("A Gathering of Foes“ 2001, "Fury“ 2008, "The Skald“ 2012 and "The Axe era“, 2014). It is based on the Old Icelandic "Sturlunga saga“, in particular, on "The Saga of Icelanders“ by Sturla Thordarson. The writing technique in the tetralogy s nevertheless antipodal to the saga manner: the events are described fragmentary, from the subjective point of view of a variety of persons, also the episodical ones; thus the complexity and the multifaceted character of the historical prcess is being stated. In each novel of the tetralogy there is one central character, the other narrators reflect upon. Snorri Sturluson, the most iconic figure of this era, is often mentioned, but is never among the narrators. The writing of sagas is being described (especially in "The Skald“), and the inner intentions of the 13th century scribes creating their texts turn out to be similiar to the intentions of modern authors. The narration manner and the universal thinking way of thecharacters neutralizes the historical distance between the narration and the readers. In modern Icelandic literature a firm narrative tradition of perception of the Sturlung era is absent, thus, the works of Einar K?rason can be regarded as the direct reception of the Old Icelandic sourse texts as they are, but not as an interplay with a set tradition of their perception. But such a tradition can be formed in future by this tetralogy.